Cytokinins from Marine Green Alga, Caulerpa raceniosa (Kuetz) Taylor - P., Kaladharan; N., Sridhar (Fishery Technology, 2025)
Cytokinin - like substances were extracted from green seaweed, Caulerpa racemosa and purified using an ion exchange column of CM-cellulose. Bioassay of these extracts with darkgerminated cotyledons of cucumber for chlorophyll biosynthesis proved the presence of cytokinin - like substances in the extract of C. racemosa. The efficiency of the extract was comparable to that of commercially available kinetin. The study is indicative of strong possibilities of producing cytokinin from unutilized and commonly occurring C. racemosa on a commercial scale and at low cost.